2017
DOI: 10.1007/s00359-017-1171-y
|View full text |Cite
|
Sign up to set email alerts
|

Route simulations, compass mechanisms and long-distance migration flights in birds

Abstract: Bird migration has fascinated humans for centuries and routes crossing the globe are now starting to be revealed by advanced tracking technology. A central question is what compass mechanism, celestial or geomagnetic, is activated during these long flights. Different approaches based on the geometry of flight routes across the globe and route simulations based on predictions from compass mechanisms with or without including the effect of winds have been used to try to answer this question with varying results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 106 publications
(281 reference statements)
2
40
0
Order By: Relevance
“…Especially challenging situations are met by using any of the alternative compasses in high arctic regions (e.g., Åkesson et al, 2001a;Muheim et al, 2003Muheim et al, , 2018. Recently, a comparative study evaluating route simulations demonstrated potential use across the widest latitudinal range for the magnetic compass (i.e., magnetoclinic route; Åkesson and Bianco, 2017).…”
Section: Spacementioning
confidence: 99%
“…Especially challenging situations are met by using any of the alternative compasses in high arctic regions (e.g., Åkesson et al, 2001a;Muheim et al, 2003Muheim et al, , 2018. Recently, a comparative study evaluating route simulations demonstrated potential use across the widest latitudinal range for the magnetic compass (i.e., magnetoclinic route; Åkesson and Bianco, 2017).…”
Section: Spacementioning
confidence: 99%
“…Changes associated with the apparent path of the sun across the sky affect daily and seasonal patterns of behavior for many animal groups, including insects, crustaceans, amphibians, reptiles, mammals, and birds (Duangphakdee et al, 2009;Dingle, 2014;Lebhardt and Ronacher, 2014;Vogt et al, 2014;Mason, 2017;Warren et al, 2019). Cues from the sun, photoperiod and light polarization, for example, are processed along with other environmental characteristics, such as magnetic fields (Dreyer et al, 2018), weather, and biological time-keeping mechanisms to determine migration phenology by a variety of species (Helm et al, 2013;Åkesson and Bianco, 2017;Muheim et al, 2018). In monarchs, an internal circadian timekeeper is combined with a sense of the sun's horizontal (azimuthal) position into a time-compensated sun compass that helps maintain a consistent bearing during the migration (Perez et al, 1997;Mouritsen and Frost, 2002;Reppert and de Roode, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that different compass systems are prioritised differently depending on environmental circumstances. For example, the sun compass route may explain migration trajectories starting at high latitudes, but in contrast to the magnetoclinic route, it fails to explain routes starting nearer to the equator 52 . A magnetic compass based on magnetoclinic routes 50 , however, seems to function across a larger span of latitudes including starting points nearer to the equator 52 .…”
Section: Departing In Time In Anticipation Of Future Environmental Cmentioning
confidence: 99%